Corruption and Corporate Innovation. (November 2020) - Ellis, Jesse; Smith, Jared; White, Roger
Abstract : We examine whether political corruption impedes innovation. Using a comprehensive sample of U.S. firms, we find that corruption has a substantial, negative relation with the quantity and quality of innovation. These results are robust to using various fixed effects, proxies for corruption and innovation, and subsamples. To establish causality, we employ 2 instruments for corruption: local ethnic diversity and the corruption of the state a firm's founder grew up in. Corruption appears to reduce innovation output both on average and for the most innovative firms. Overall, this evidence is consistent with the notion that corruption reduces social welfare by impeding innovation.